2017
DOI: 10.1177/0305735617715515
|View full text |Cite
|
Sign up to set email alerts
|

Improvised song endings in a developmental perspective: A mixed-methods study

Abstract: The aim of this mixed-methods study was to investigate the development of children’s improvised song endings over the course of two years, through researcher-led tasks. While quantitative data were used to examine the roles of age, biological sex, and music training on children’s improvised song endings and pitch-matching skills, qualitative data were gathered to shed light on the musical contents of improvisations, the strategies used by children when improvising, and children’s reactions to different improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…A study could also be designed where the workshop leader steps away from the group to investigate what musical interactions occur without an adult present. Results from this study should not be viewed in the same light as models showing a linear progression through increasing skill in manipulating musical parameters (e.g., Ilari et al, 2017). The order in which the children progressed through parameters in this study, although interesting, is not as important as appreciating that the children showed CMA and S-MA in a range of different parameters of their own choosing.…”
Section: Evaluated Children's Improvisation On Criteria Includingmentioning
confidence: 64%
“…A study could also be designed where the workshop leader steps away from the group to investigate what musical interactions occur without an adult present. Results from this study should not be viewed in the same light as models showing a linear progression through increasing skill in manipulating musical parameters (e.g., Ilari et al, 2017). The order in which the children progressed through parameters in this study, although interesting, is not as important as appreciating that the children showed CMA and S-MA in a range of different parameters of their own choosing.…”
Section: Evaluated Children's Improvisation On Criteria Includingmentioning
confidence: 64%
“…Our musical improvisation continuation task is modeled after previous studies and is designed to be doable by participants of all levels of training (Pinho et al, 2014; Ilari et al, 2017). Like all creative tasks, there is no unique correct answer for each trial, but some utterances are clearly more creative than others.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report the first results from a combined behavioral and neuroimaging study to test the hypothesis that individual differences in creative musical behavior are associated with differences in gray matter structure. We use a behavioral task of musical improvisation to assess real-time creativity in individuals with a broad range of musical training, similar to recent studies from a developmental perspective (Ilari et al, 2017). Expert ratings of musical creativity are used as predictors in a voxel-based morphometry (VBM) study to relate gray matter structure to musical improvisation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The second AIRS-TBSS task, improvisation, was used to measure vocal creativity in which participants were asked to vocally improvise a musical answer on the syllable “la”. Three independent raters with a mean of 14.5 years of musical experience awarded scores to participants’ responses as follows (Ilari et al, 2017): no response was awarded a score of 0; a response consisting only of a few notes or a repetition of part of the phrase was awarded 0.5; an imitation of the entire phrase was awarded 1; a slightly varied imitation was awarded 2 and a variation of the original in which there were four or more different notes was awarded 3. Inter-rater, split-half reliability was good at both at pre-testing ( r =.81) and post-testing ( r =.85).…”
Section: Methodsmentioning
confidence: 99%
“…Lewinski et al (2014) found the program to be accurate for matching scores of 89% in adult faces. While emotional perceptions of music education tasks are often assessed by means of survey methods (Ilari et al, 2017), it can be difficult to collect survey responses from children. In addition, such responses may not accurately reflect children’s perceptions (Erickson & Schulkin, 2003).…”
Section: Methodsmentioning
confidence: 99%